2021
DOI: 10.1016/j.actbio.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Clustering of Adhesion Ligands in Nanofiber-Nanoparticle Composites

Abstract: Because the positioning and clustering of biomolecules within the extracellular matrix dictates cell behaviors, the engineering of biomaterials incorporating bioactive epitopes with spatial organization tunable at the nanoscale is of primary importance. Here we used a highly modular composite approach combining peptide amphiphile (PA) nanofibers and silica nanoparticles, which are both easily functionalized with one or several bioactive signals. We show that the surface of silica nanoparticles allows the clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…This successfully enhanced fibroblast adhesion and spreading when incorporating biofunctionalized SiNPs similar to those used here (i.e. SiNP-RGDS, SiNP-PHSRN and SiNP-RGDS+PHSRN) [29]. In this case, the use of peptide amphiphiles as ECM building blocks instead of collagen decreased the impact of sulfonate-modified particles as no strong interaction with the matrix was expected.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This successfully enhanced fibroblast adhesion and spreading when incorporating biofunctionalized SiNPs similar to those used here (i.e. SiNP-RGDS, SiNP-PHSRN and SiNP-RGDS+PHSRN) [29]. In this case, the use of peptide amphiphiles as ECM building blocks instead of collagen decreased the impact of sulfonate-modified particles as no strong interaction with the matrix was expected.…”
Section: Discussionmentioning
confidence: 69%
“…Synergistic interactions are known to be effective only for a peptide inter-distance of ca. 5 nm, which can happen when both peptides are statistically distributed at SiNP surface [29]. To fulfill this requirement, SiNPs were synthesized bearing one of these two peptide sequences (SiNP-RGDS, SiNP-PHSRN), or bifunctionalized with both peptides (SiNP-RGDS-PHSRN) (Figure 3c).…”
Section: Obtaining Self-supported Collagen Filmsmentioning
confidence: 99%
“…Synergistic interactions are known to be effective only for a peptide inter-distance of ca. 5 nm, which can happen when both peptides are statistically distributed at SiNP surface [ 29 ]. To fulfill this requirement, SiNPs were synthesized bearing one of these two peptide sequences (SiNP-RGDS, SiNP-PHSRN), or bifunctionalized with both peptides (SiNP-RGDS-PHSRN) ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…This includes the RGDS peptide sequence within fibronectin, which synergizes with the PHSRN sequence in a distance-dependent manner, substantially enhancing cell adhesion mediated by the α5 β1 integrin receptor for fibronectin [ 27 , 28 ]. We have recently reported that surface modification of SiNPs can be successfully used to simultaneously display RGDS and PHSRN enabling enhanced cell adhesion and spreading [ 29 ]. Significant advances for regenerative medicine can be expected by coupling signaling abilities with fine control over structure.…”
Section: Introductionmentioning
confidence: 99%
“…on two different SiNP populations. 32 Despite these key results, it remains difficult to precisely determine the inter-peptide distance at the surface of the particles, a key to achieve in order to faithfully reproduce the organization of living systems. To address this challenge we propose here to use chemically-modified colloidal gold as tag to reveal the position of amine groups on nanosurfaces taking advantage of the robustness and specificity of peptide-like coupling.…”
Section: Introductionmentioning
confidence: 99%